A systematic review of randomised controlled trials examining the therapeutic effects of adult bone marrow-derived stem cells for non-ischaemic dilated cardiomyopathy. Issue 1 (December 2016) - Lu, Yi; Wang, Yiqin; Lin, Menglu; Zhou, Jiale; Wang, Zi; Jiang, Meng; He, Ben
Abstract Background Certain early-phase clinical trials have suggested that bone marrow-derived stem cell transplantation might improve left ventricular function in patients with non-ischaemic dilated cardiomyopathy (NIDCM), whereas others trials have revealed no benefit from this approach. We sought to evaluate the therapeutic effects of bone marrow-derived stem cell therapy on NIDCM. Methods We searched the PubMed, Embase, and Cochrane Central Register of Controlled Trials (CENTRAL) databases (through February 2016) for randomised controlled clinical trials that reported on bone marrow-derived stem cell transplantation for patients with NIDCM with a follow-up period ≥12 months. The co-primary endpoints were changes in mortality rate and left ventricular ejection fraction (LVEF); the secondary endpoints were changes in the 6-minute-walk test (6MWT) and left ventricular chamber size. Seven trials involving bone marrow-derived stem cell therapy that included 482 patients satisfied the inclusion and exclusion criteria. Results Subjects who received bone marrow-derived stem cell therapy exhibited a significant reduction in mortality rate (19.7% in the cell group vs. 27.1% in the control group; 95% confidence interval (CI) –0.16 to –0.00, I 2  = 52%, p  = 0.04). Bone marrow-derived stem cell therapy tended to produce LVEF improvement within 6 months (1.83% increase; 95% CI –0.27 to 3.94, I 2  = 74%, p  = 0.09) and significantly improved LVEF after mid-term (6–12 months) follow-up (3.53% increase; 95% CI 0.76 to 6.29, I 2  = 88%, p  = 0.01). However, this therapy produced no significant benefit in the 6MWT (p  = 0.18). Finally, the transplantation of increased numbers of stem cells resulted in no observable additional benefit with respect to LVEF. Conclusions Bone marrow-derived stem cell therapy might have improved prognoses and appeared to provide moderate benefits in cardiac systolic function at mid-term follow-up. However, this therapy produced no observed improvement in exercise tolerance.